Practical straw bale building - Hollis, Murray (Landlinks Press, 2005)
Building with straw bales is being embraced by amateurs and professionals for its versatility, comfort, environmental friendliness and high insulation. Practical Straw Bale Building describes the best of current practices and introduces new ideas in a practical step-by-step approach, supported by technical data and analysis.